To win the future : people empowerment for national development - Ramos, Fidel V. (Manila, Philippines : Friends of Steady Eddie, 1993)
This collection of my speeches is published on the initiative of friends who felt the need for a public record of the priorities, policies and programs of my administration this early term.
1. Road to the Presidency -- 2. Program of government -- 3. The Economy -- 4. Government and development -- 5. Social issues -- 6. Foreign relations.
"A collection of speeches by the President of the Republic of the Philippines."
Includes index.
Keywords: PHILIPPINES -- POLITICS AND GOVERNMENT